2008
DOI: 10.1097/coc.0b013e318145b98b
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lung Cancer Patients by Serum Protein Profiling Using Surface-Enhanced Laser Desorption/Ionization Time-of-Flight Mass Spectrometry

Abstract: The results suggest that SELDI time-of-flight mass spectrometry technique can correctly distinguish lung cancer patients from healthy individuals and shows great potential for the development of a screening test for the detection of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…We, on the other hand, observed decreased C3a desArg levels in breast cancer in the current study population, as well as in a subset thereof, which we analysed for validation of the 8.9 kDa marker reported by Li et al (21). Other studies have described decreased 8.9 kDa peak intensities in breast (7,38), and lung cancer (39). Moreover, Li et al observed decreased SELDI-TOF MS C3a desArg peak intensities in sera of metastatic breast cancer patients (10).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We, on the other hand, observed decreased C3a desArg levels in breast cancer in the current study population, as well as in a subset thereof, which we analysed for validation of the 8.9 kDa marker reported by Li et al (21). Other studies have described decreased 8.9 kDa peak intensities in breast (7,38), and lung cancer (39). Moreover, Li et al observed decreased SELDI-TOF MS C3a desArg peak intensities in sera of metastatic breast cancer patients (10).…”
Section: Discussionmentioning
confidence: 57%
“…Although peak intensities of both m/z 5350 and m/z 28183 were not significantly different in expression between breast cancer and healthy control, combination with other markers evidently improved their diagnostic performance. The m/z 5350 peak cluster, though not structurally identified, has been reported earlier as significantly increased in sera of patients with lung cancer (39) and hypopharyngeal squamous cell carcinoma (46). Based on the observed mass, we hypothesise the m/z 28183 peak cluster to represent apolipoprotein A-I.…”
Section: Itih4 Fragmentsmentioning
confidence: 99%
“…Biomarkers for colon and pancreatic cancers are found in fecal samples. Techniques for biomarker discovery include genome sequencing, arrays and differential display-related methods, proteins and phosphoproteins, antibodies, electrophoretic 2D gels, and nuclear magnetic resonance spectroscopy [67].…”
Section: Future Oncotarget Related Basic Research and Therapeuticsmentioning
confidence: 99%
“…Although the fragment is directly correlated with serum coagulation in healthy individuals (2 ), its presence in samples from diseased individuals is likely due to the same mechanism. Despite numerous reports of its identification and correlation with the coagulation process, FIBA 5909 continues to be rediscovered and reported as "uncharacterized" (11 ). Remaining current with the biomarker literature has grown increasingly difficult over the years, with the growth of the field and the advent of new journals sharing the responsibility.…”
mentioning
confidence: 99%